2008
DOI: 10.1002/marc.200890038
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Rapid Commun. 19/2008

Abstract: Cover: The image shows a hybrid polymeric scaffold that was fabricated using a rapid prototyping (RP) method and electrospinning process. The panels clearly indicate that the layers of electrospun micro-/nanofibers are located between the layers of dispensed poly("-caprolactone) strands. Further details can be found in the article by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…The result is coincident with that of Sachlos and Czernuszka, who reported that increasing the pore size or porosity decreases the compressive modulus of the scaffold [3]. Recently, the RP process was combined with various fabrication processes, such as electrospinning [11,12] and freeze-drying techniques [13], and the fabricated hybrid scaffolds improved initial cell attachment and proliferation as compared to a general 3-D scaffold. Detailed comparisons for various 3-D scaffold fabricating methods including RP technology have been well described in Ref.…”
Section: Introductionsupporting
confidence: 83%
“…The result is coincident with that of Sachlos and Czernuszka, who reported that increasing the pore size or porosity decreases the compressive modulus of the scaffold [3]. Recently, the RP process was combined with various fabrication processes, such as electrospinning [11,12] and freeze-drying techniques [13], and the fabricated hybrid scaffolds improved initial cell attachment and proliferation as compared to a general 3-D scaffold. Detailed comparisons for various 3-D scaffold fabricating methods including RP technology have been well described in Ref.…”
Section: Introductionsupporting
confidence: 83%
“…These nanofibrous structures have been widely explored for use in tissue engineering due to their high porosity and good surface area-to-volume ratio as well as their topographical features which enhance cellular adhesion, migration, and proliferation. [12][13][14] Since the nanofiberous scaffold is extremely long, entangled, and densely packed into a 2-D structure on the surface, it is difficult for the electrospun nanofibers to be shaped into porous 3-D architecture for tissue engineering scaffold. In order to produce a highly macroporous construct that also provides a nanofibrous structure, we first developed PLLA nanocylinders by aminolysis and ultra-sonication process.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, electrospinning of bioerodible polymers is well known. There are not many efforts in the literature to make short electrospun fibers 40. Previously we used mechanical cutting, UV cutting method for getting short fibers 41, 42…”
Section: Introductionmentioning
confidence: 99%